The Correlation Of Islamic Civilization In Sciences With Western World ( Eastern Impact Through Sciences On Western World ) - Said, Mohamed Mohamed Tolba (2018)
The nature of scientific verification of knowledge distinguishes it from mystical knowledge in empirical sciences. Islam is a religion and a civilization, historically connecting various stages of human history for more than fourteen centuries. The Islamic ethics and law “Sharia’h” are coherent legal system to protect private property within a comprehensive and rational system. Capitalism and the industrial revolution of western world dramatically transformed resulting in a socio-economic schism consequently emerged as a domineer for existence and affected the Islamic world. The secular and rationalized legal framework needed capitalism, which is incompatible with the nature of Islamic law. The western science in this civilization is also separated from morality and noble values because it has adopted materialistic philosophies and ideologies, such as Pragmatism, Darwinism, Existentialism and any other philosophy that is against the Islamic religion.